Analisis Kesiapan Tenaga Kesehatan di Kota Lahat dalam Menghadapi Sistem Informasi Sumber Daya Manusia (SISDM) - Aklin Agusra; Dina Mellita; Heriyanto Heriyanto; Efan Elpanso (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the level of readiness of health workers in facing the implementation of the Human Resources Information System (SISDM) at Lahat City Hospital. The background of the research is based on the suboptimal implementation of SISDM, which is characterized by the low familiarity of some health workers with the system, data input errors, and incomplete system integration. The research method used was quantitative with an associative approach, involving 72 State Civil Apparatus (ASN) health workers selected through cluster sampling techniques. Data analysis was carried out using logistic regression to identify factors affecting readiness. The results of the study show that in general, the readiness of health workers is in the high category, with an average indicator score above 4. Key factors that support readiness include organizational support, adequate training, and a positive attitude toward technology. The variable length of work has the most significant influence on readiness, with an Exp(B) value of 38.826, which indicates that the longer the work experience, the higher the readiness to adopt SISDM. These findings confirm that work experience is an important asset in the process of information technology adaptation. Although healthcare workers are declared ready, the study recommends increased optimization of technology tools and ongoing training as a strategic step to ensure the successful implementation of comprehensive and sustainable SISDM in the hospital environment.